Persepsi Mahasiswa Terhadap Pembelajaran Kewirausahaan Dalam Membentuk Kesiapan Berwirausaha Mahasiswa Program Studi Pendidikan Ekonomi Universitas Jambi - Subaidah; Refnida; Rayana Siregar, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of entrepreneurship learning in shaping students' entrepreneurial readiness. Although entrepreneurship learning has provided knowledge, experience, and motivation, the practical experience gained by students still needs to be strengthened. This study aims to describe the perceptions of students in the Economics Education Study Program at the University of Jambi regarding entrepreneurship learning in shaping entrepreneurial readiness. This study used a qualitative approach with a phenomenological research type. Data were collected through interviews, observations, and documentation with six students who had taken entrepreneurship courses and one lecturer teaching entrepreneurship courses. Data analysis used the Miles, Huberman, and Saldaña model with the help of NVivo 12, while data validity was tested through source triangulation and technical triangulation. The results showed that students have a positive perception of entrepreneurship learning. This perception is reflected in the importance of entrepreneurship learning, the development of ideas and creativity, the practical benefits of learning, and the suitability and application of the material. Entrepreneurship learning is seen as being able to increase knowledge, creativity, self-confidence, and entrepreneurial readiness. However, students also assessed that practical experience still needs to be improved to make the learning more applicable. Thus, entrepreneurship learning contributes to shaping the entrepreneurial readiness of students in the Economics Education Study Program at the University of Jambi.